Halal Consumer Protection in The Digital Era: Blockchain Certificates as Legal Evidence - Nurul Islami; Zulfiqar Bhisma Putra Rozi (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2026)
The rapid development of e-commerce has accelerated the circulation of products claiming halal certification. It has also shifted halal product distribution patterns to the digital realm. This shift raises issues related to verification and protection of consumer rights. Blockchain-based electronic evidence in the context of halal certification has become a fundamental issue for muslim consumer protection in the digital era. There are incomplete regulations governing the status and mechanisms for verifying blockchain evidence. These gaps pose challenges in providing evidence in court and create legal uncertainty for consumers. This study aims to analyze the validity of blockchain-based halal certificates as a legal evidentiary tool in consumer protection disputes. The goal is to strengthen muslim consumer protection in Indonesia. This study is a normative legal study using statutory and conceptual approach. The legal materials were obtained from primary and secondary sources by examining the Halal Product Guarantee Law, the Consumer Protection Law, and regulations related to electronic information. The analysis was conducted through systematic interpretation and literature review. The research results show that blockchain-based halal certificates have potential probative validity due to their transparency and decentralization. This can increase the transparency and authenticity of halal products. However, in practice, there are still no technical guidelines regarding the blockchain-based halal certificate verification mechanism. Therefore, comprehensive special regulations are needed from the government, particularly technical guidelines for blockchain-based halal certification, to ensure consumer protection in the digital era. their transparent and decentralized nature, which can enhance the transparency and authenticity of halal products.